Efeitos da lesão do núcleo do trato solitário comissural sobre a ingestão de água e sólido - Blanch, Graziela Torres (2005)
The central nervous system (CNS) has an important function in the regulation of homeostatic mechanisms controlling the volemia and osmolality of the body fluid. The nucleus of the tract solitary (NTS) is the primary site of the cardiovascular afferents and peripheral osmoreceptors. From to NTS, the information about arterial blood pressure, extracellular fluid composition and volume goes to other areas into the CNS involved to cardiovascular regulation and hydroeletrolytic balance, e.g., anteroventral third ventricle region (AV3V), paraventricular nucleus of hypothalamus, lateral parabrachial nucleus (LPBN) and the vasomotors nuclei of medulla. The NTS can be anatomically divided in rostral NTS, intermediate NTS and commissural NTS (commNTS). Therefore, the aims of this study were: a) to study the effects of acute and chronic electrolytic lesion of the commNTS on the water and 0.3 M NaCl intake induced by different protocols that induced intracellular and/or extracellular dehydration, b) to study the possible mechanisms which commNTS lesion induce changes in water and/or sodium intake, evaluating the hemodynamic and renal changes. Male Holtzman rats (300-320g) were submitted to commNTS or sham lesion. The animals were anesthetized and placed in a stereotaxic apparatus. Through a partial craniotomy of the occipital bone, the dura mater and arachnoid were incised, and the dorsal surface of the brain stem was exposed. Electrolytic lesions were performed with a tungsten electrode inserted into the brain stem following coordinates: 0.0 mm lateral, 0.4, 0.7 and 1.0 mm posterior to the calamus scriptorius, and 0.1 mm below the dorsal surface of the brain. The electrolytic lesions were performed with 1 mA current delivered for 5 seconds, twice with a 30 s interval between them. Sham-operated rats underwent the same procedures, but no current was passed. Initial body weight was the same, but commNTS lesioned rats had a significant loss in the weight compared with sham rats during the 14 days. The pressor response of the chemoreflex, tested with potassium cyanide iv, was reduced in chronic commNTS lesioned rats, whereas the baroreflex tested with phenylephrine and sodium nitroprusside was unchanged in commNTS lesioned rats. The water intake induced by intragastric (ig) gavage of 2 M NaCl was greater in acute and chronically commNTS-lesioned rats compared to sham rats. There was no 0.3 M NaCl intake after ig gavage of 2 M NaCl in lesioned or sham rats. Acute and chronically, the treatment with furosemide (diuretic) and captopril (ANG II converting enzyme inhibitor)